2017
DOI: 10.1038/tp.2017.27
|View full text |Cite|
|
Sign up to set email alerts
|

Premature primary tooth eruption in cognitive/motor-delayed ADNP-mutated children

Abstract: A major flaw in autism spectrum disorder (ASD) management is late diagnosis. Activity-dependent neuroprotective protein (ADNP) is a most frequent de novo mutated ASD-related gene. Functionally, ADNP protects nerve cells against electrical blockade. In mice, complete Adnp deficiency results in dysregulation of over 400 genes and failure to form a brain. Adnp haploinsufficiency results in cognitive and social deficiencies coupled to sex- and age-dependent deficits in the key microtubule and ion channel pathways.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
77
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(88 citation statements)
references
References 58 publications
5
77
0
6
Order By: Relevance
“…Tauclearance therapies [15] are also being developed, however, Tau monotherapy may not suffice [44,45]. Importantly, it is apparent that the various tauopathies constitute different diseases, which may require versatile treatment modalities [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tauclearance therapies [15] are also being developed, however, Tau monotherapy may not suffice [44,45]. Importantly, it is apparent that the various tauopathies constitute different diseases, which may require versatile treatment modalities [15].…”
Section: Discussionmentioning
confidence: 99%
“…Soluble tau damages the morphology and connectivity of newborn granule cells [54] and NAP/ADNP enhance Tau-MT association and dendritic spine formation in an EB1/EB3dependent manner [23,25]. Furthermore, Tau aggregation is inhibited by augmented autophagy [55], and ADNP/ NAP accelerate autophagy [14,15,19,[56][57][58][59]. As tauopathy is suggested to propagate in a prion-like manner [60][61][62], it is hypothesized that even rare occurrences of cellular tauopathy will propagate, making prevention therapy with NAP treatment prior to disease onset a desired possibility.…”
Section: Discussionmentioning
confidence: 99%
“…Besides classic neurotransmitters (biogenic amines and amino acids), there are other signaling molecules involved in neuronal communication. Some of the most relevant include ADNP (activity-dependent neuroprotective protein) that regulates axonal transport (Gozes et al 2017), Spermine (Spermine synthase deficiencies produce intellectual disability), X-linked Synder-Robinson type (Pegg 2014), and BDNF (brain-derived neurotrophic factor). BDNF is the most known neurotrophin in the brain which plays an important role in synaptogenesis and synaptic plasticity mechanisms.…”
Section: Other Signaling Moleculesmentioning
confidence: 99%
“…Together with additional point/frameshift truncating mutations identified in autistic patients, all of whom suffered from intellectual deficiencies, delayed developmental milestones including motor function development and shared characteristic facial features, it was concluded that mutations in ADNP cause a syndromic form of autism. A short summary of the clinical phenotype was recently published including the observation that most ADNP syndrome children also exhibit early primary tooth eruption . Importantly, a systematic variant annotation approach for ranking genes associated with ASDs classified ADNP as one of three most prevalent autism‐causing genes (including SHANK3 and CHD8 ) …”
Section: Adnp and Autophagy: Autismmentioning
confidence: 99%
“…Future clinical studies are planned for the ADNP syndrome by Coronis Neurosciences (http://www.coronisns.com/). The syndrome mimics our Adnp‐deficient (heterozygote) mouse model, displaying cognitive and social deficits, which are reversed, in part by the ADNP 8‐amino‐acid snippet NAP (NAPVSIPQ) − Coronis lead compound (CP201), as well as by SKIP (CP102), which reversed BECN1 reduced expression in the female Adnp‐deficient mouse hippocampus …”
Section: Adnp and Autophagy: Autismmentioning
confidence: 99%